2021
DOI: 10.26466/opus.906143
|View full text |Cite
|
Sign up to set email alerts
|

Lise Öğrencilerinde Öz-Şefkat ile Duygusal Özerklik Arasındaki İlişkide Erken Dönem Uyumsuz Şemaların Aracı Rolü

Abstract: Uyumsuz Sȩma Ölçekler Takımı ile toplanmıştır. Araştırmada öz-şefkat, duygusal özerklik ve erken dönem uyumsuz şemalar arasındaki ilişkiler regresyona dayalı aracılık analizi ve korelasyon analizi ile incelenmiştir. Ayrıca, test edilmeye çalışılan aracı modeldeki doğrudan ve dolaylı etkiler bootstrap yöntemi ile belirlenmiştir. İlgili alanyazın ışığında, şema alanları dikkate alınarak aracılık modelleri kurulmuş ve bu doğrultuda erken dönem uyumsuz şemaların aracı rolü sınanmıştır. Araştırma sonucunda erken dö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…Among the specified schema areas, the rejection schema area can be encountered as a result of not meeting basic needs, and failure and enmeshment schemas as a result of overprotective or neglectful parental attitudes (Young et al, 2003). Studies have shown that emotional deprivation and self-compassion mediate emotional autonomy (Koçak & Çelik, 2021). Zeze has always been one of the best students throughout his education life, but he did not do this within the framework of perfectionism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the specified schema areas, the rejection schema area can be encountered as a result of not meeting basic needs, and failure and enmeshment schemas as a result of overprotective or neglectful parental attitudes (Young et al, 2003). Studies have shown that emotional deprivation and self-compassion mediate emotional autonomy (Koçak & Çelik, 2021). Zeze has always been one of the best students throughout his education life, but he did not do this within the framework of perfectionism.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, Brazilian people are more likely to be distant to the concept of self-compassion. It is assumed that this situation, which is desired to be seen in society, may negatively affect the development of self-compassion (Koçak & Çelik, 2021). While Zeze was very affectionate towards his own brother Luis, he displayed a similar attitude to himself less frequently.…”
Section: Resultsmentioning
confidence: 99%
“…Bu çalışmada, bireylerin öz-anlayış puanları ile duygusal şemaları arasında negatif yönlü anlamlı ilişkiler olduğu tespit edilmiştir. Alanyazında bu sonucu destekleyen benzer araştırmalar mevcuttur (Güzey, 2020;Koçak & Çelik, 2021;Thimm, 2017;Yakin et al, 2019). Germer'in (2020) erken dönem uyumsuz şemaların bireylerin öz-anlayış gücünü tam olarak kullanma yeteneğini olumsuz etkilediğine yönelik tespiti de bu sonucu destekler niteliktedir.…”
Section: Tartışma Ve Sonuçunclassified